(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The present investigation work summarizes the development of irinotecan liposome injection for intravenous infusion, 4.3 mg/mL (10 mL fill), a generic equivalent of reference product onivyde irinotecan liposome injection for intravenous infusion, 4.3 mg/mL (10 mL fill), which is indicated for colorectal cancer dosing for camptosar. Quality by design (QbD) approach has been used to develop generic irinotecan liposome injection and manufacturing process that ensures the quality, safety and efficacy of irinotecan liposome injection. Preliminary screening trials for drug (API) loading suggest that active loading process with extrusion process using ammonium dihydrogen phosphate shows better drug entrapment with less free drug. A 2(5-1) fractional factorial design of experiments (DoE) adopted to evaluate the effect of lipids concentration in ethanol, hydration temperature, hydration time, extruder temperature and extruder pressure on particle size. Based on design space, optimized process parameters were defined for maintaining the required particle size. A 2(4-1) fractional factorial DoE adopted to evaluate the drug loading heating temperature, drug loading heating time, drug loading cooling temperature and drug loading cooling time on particle size and free drug. Based on design space, optimized process parameters were defined for maintaining the required particle size and % free drug. Stability study of the final formulation suggest no any degradation of impurity and no any % free drug is increasing with respect to stability time. Also all characterization was performed on final formulation and all data is comparable with the reference formulation. The developed formulation of irinotecan liposome injection for intravenous infusion, 4.3 mg/mL (10 mL fill) shows less free and high entrapped drug compared to reference product with new remote loading agent except patent of onivyde.